Leadership Styles in Managing Change Among Healthcare Professionals: A Systematic Literature Review - Norizun Mohd Noor; Azimah Ahmad; Soon Lean Keng (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2025)
Leadership styles critically shape healthcare professionals’ readiness for organizational change, yet the evidence on which styles most effectively reduce resistance remains fragmented. Following PRISMA 2020 guidelines, we used the PICO framework to develop search strategies. Searches (January 2020–March 2024) were conducted in SCOPUS, Web of Science, Google Scholar, ProQuest, CINAHL, Medline, EMBASE (OVID), and Cochrane, limited to English-language empirical studies. Search terms included leadership, change, and resistance to change. Data were synthesized using content analysis. From 1,263 records, 10 studies met the inclusion criteria. Quantitative synthesis showed 70% supported transformational leadership as most effective, with idealized influence, inspirational motivation, and intellectual stimulation enhancing change readiness. 20% favored democratic/participative leadership for improving communication and shared decision-making. 10% endorsed transactional leadership, effective in structured change requiring clear performance metrics and contingent rewards. Across all studies, leadership style influenced employee attitudes, willingness to change, and resistance levels. Transformational leadership predominates in reducing resistance and fostering readiness, though democratic and transactional approaches may suit specific contexts. Findings highlight the need for adaptive, context-sensitive leadership strategies to optimize change outcomes.